KECEPATAN PUTARAN DAN FREKUENSI GENERATOR PADA KONDISI BEBAN TIDAK SEIMBANG - - Asmar; Sasongko Pramono Hadi; - T. Haryono (MEDIA ELEKTRIKA, 2014)
Load imbalance caused instantaneous power generator contains components sinusiodal. There is a difference of energy between the stator and rotor always. The energy difference must be balanced by the rotor by means of decrease or increase speed. This gives rise to oscillations in the power angle, frequency and rotation speed of the generator. To determine the oscillation amplitude of the power angle, the instantaneous power generator should be expressed as a function of power angle. This is done by the method of symmetrical components. Angle at steady state power is the amount of power angle caused by the active power and the generator power angle caused by sinusiodal components. The frequency and speed of rotation angle based power generator is known. Oscillation frequency and rotation speed of the generator is affected by the power generated by the negative sequence components, generator inertia constant and damping factor. Keywords: Imbalance, symmetrical components, instantaneous power, power angle, frequency, speed of rotation.